Amylase polymorphism affects growth in the cupped oyster Crassostrea gigas - Huvet, Arnaud; Samain, Jean-francois; Boudry, Pierre; Bedier, Edouard; Ropert, Michel; Van Wormhoudt, A. (Actes International Coneference on Shellifsh Restoration, Brest, France 2-5 Octobre 2005, 12 p., 2005)
The better understanding of physiological and environmental factors that determine optimal food conversion efficiencies is of major interest for the cupped oyster Crassostrea gigas for which the strong increase of aquaculture has been correlated in France with a decrease in productivity due to competition between aquatic species for limited food supplies at grow-out sites. To investigate the non-neutrality of the polymorphism of amylase, a key enzyme for carbohydrate assimilation, in oyster physiology, we report in the present paper the growth and survival measurement of amylase genotypes within five bi-parental C. gigas families, bred to be polymorph at the two PCR-RFLP amylase markers, and reared over one year under standard culture conditions in two French aquaculture areas. For growth, amylase genotypes within three families have shown differences of total weight and meat wet weight mainly significant in one location. The amylase polymorphism affects C. gigas growth and we can assume that differences of growth between genotypes are expressed depending on the environment. Considering that no differences of survival were observed between genotypes within family, this variability of growth can lead to a gain of yield. For biggest differences between genotypes within family, enzymatic parameters were analyzed. The specific amylase activity appeared significantly different between the genotypes within one family and positively correlated to differences in weights. Specific amylase activity was therefore affected by amylase polymorphism and may partly explain growth difference observed between amylase genotypes in this experiment. The correlation between amylase polymorphism and growth in the cupped oyster C. gigas has suggested the interest of using the amylase markers for selective breeding program in oyster.